2014
DOI: 10.1021/jf504221x
|View full text |Cite
|
Sign up to set email alerts
|

Using Molecular Tools To Decipher the Complex World of Plant Resistance Inducers: An Apple Case Study

Abstract: Exogenous application of plant resistance inducers (PRIs) able to activate plant defenses is an interesting approach for new integrated pest management practices. The full integration of PRIs into agricultural practices requires methods for the fast and objective upstream screening of efficient PRIs and optimization of their application. To select active PRIs, we used a molecular tool as an alternative to methods involving plant protection assays. The expressions of 28 genes involved in complementary plant def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…However, fitness benefits have been observed on primed plants in the field under high disease pressures as the energy of the plant remains devoted to its development until a biotic stress actually occurs [27,28]. In the present case, we used H 2 O 2 to mimic a biotic stress comparable to a Z. tritici infection, as described by Dugé de Bernonville et al [24]. Hydrogen peroxide is indeed a reactive oxygen species (ROS) which acts as a central player in the transduction of stress signals in the plant [29,30].…”
Section: Plant Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fitness benefits have been observed on primed plants in the field under high disease pressures as the energy of the plant remains devoted to its development until a biotic stress actually occurs [27,28]. In the present case, we used H 2 O 2 to mimic a biotic stress comparable to a Z. tritici infection, as described by Dugé de Bernonville et al [24]. Hydrogen peroxide is indeed a reactive oxygen species (ROS) which acts as a central player in the transduction of stress signals in the plant [29,30].…”
Section: Plant Treatmentmentioning
confidence: 99%
“…The recognition of an elicitor by the plant triggers a cascade of defense mechanisms leading to induced resistance. We thus investigated the expression of 23 defense genes of wheat in treated versus untreated plants by using an innovative biomolecular tool developed by INRA [23,24]. Such tests provided useful information regarding the defense signaling pathways preferentially triggered in the plant by surfactin.…”
Section: Introductionmentioning
confidence: 99%
“…The full integration of PRIs into agricultural practices requires methods for the fast and objective upstream screening of efficient PRIs and optimization of their application (Bernonville et al, 2014). The induction of resistance has been extensively studied in order to develop new alternatives in disease control, particularly to develop measures that will minimise the impact to the environment and to man.…”
Section: Resistance Inducersmentioning
confidence: 99%
“…Several transcript biomarkers associated with IR have been proposed. In a commendable effort by Bernonville et al [170] used 28 transcript markers to screen for novel PRIs and found correlation between the level of defense activation and protection efficiency in controlled conditions. These types of biomarker approaches have future potential and could also be used to identify genotypes with strong capacity for IR in Solanaceae .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%